Feasibility and accuracy evaluation of novel 2D instant navigation system on spinal surgery - a preclinical study - Wen Xia; Zhengyang Wu; Rui Zuo; Jiang Wu; Jing Ling; Linfeng Mo; Zegang Shi; Yue Zhou; Changqing Li; Wenjie Zheng; Chao Zhang (BMC Musculoskeletal Disorders)
Abstract Background Intraoperative navigation has significantly facilitated spinal surgery and enhanced surgical accuracy. Nevertheless, it is often encumbered by the need for expensive equipment, a complex workflow, and frequently exhibits inefficiencies. Leveraging permanent calibration technology, we have developed a novel two-dimensional fluoroscopic image navigation system with the aim of streamlining and expediting the navigation process. In this study, we comprehensively evaluated its feasibility and accuracy. Methods The accuracy of the 2D-navigation system was rigorously assessed using a standardized high-precision mold. To validate the feasibility and accuracy of the novel navigation system for spinal surgery, the bare-bones of the pig lumbar spine are employed for evaluation. Subsequently, 2D navigation-assisted pedicle penetrations were meticulously carried out on the spine (L1-L5) of live animals. The navigation accuracy was quantified by comparing the visualized position of the surgical tool in the actual fluoroscopic image with the virtual position pre-planned by the navigation system. Results During the experimental process, an excellent correlation between the virtual fluoroscopic images and actual fluoroscopic images was prominently observed. The navigation positioning accuracy, as evaluated by the standardized high-precision mold, was determined to be 0.54±0.16mm (AP view) and 0.57±0.14mm (lateral view). Specifically, in the bare-bones of the pig lumbar spine, the average distance errors between the virtual and actual fluoroscopic images under anteroposterior and lateral views were 0.99±0.48mm and 0.87±0.60mm, respectively. Meanwhile, the average angle errors were 0.41±0.29 $$^{° }$$ ∘ and 0.37±0.11 $$^{° }$$ ∘ , respectively. In the surgical procedure on normal adult pigs (L1-L5), the average distance errors were 1.14±0.58mm(95% CI [0.50-0.59]) and 1.54±0.79mm(95% CI [0.11-0.12]), respectively. The corresponding average angle errors were 0.61±0.49 $$^{° }$$ ∘ (95% CI [0.33-0.35]) and 0.40±0.31 $$^{° }$$ ∘ (95% CI [0.33-0.47]), respectively. Throughout a single navigation registration and the entire surgical procedure, the navigation accuracy across the L1 to L5 segments remained consistently high, with no statistically significant differences detected among the segments (p>0.05). Conclusion The two-dimensional fluoroscopic image navigation system based on permanent calibration technology is characterized by a rapid and convenient workflow. It demonstrates high-level navigation accuracy, thereby meeting the stringent requirements for spinal navigation in live surgical procedures.